Morphological characteristics in diabetic cardiomyopathy associated with autophagy. Issue 1 (January 2021) - Kanamori, Hiromitsu; Naruse, Genki; Yoshida, Akihiro; Minatoguchi, Shingo; Watanabe, Takatomo; Kawaguchi, Tomonori; Tanaka, Toshiki; Yamada, Yoshihisa; Takasugi, Hironobu; Mikami, Atsushi; Minatoguchi, Shinya; Miyazaki, Tatsuhiko; et al.
Highlights: Diabetic cardiomyopathy develops in the absence of coronary artery disease or hypertension. Morphological features provide new insight into the pathophysiology of diabetic cardiomyopathy. Modulating autophagy could be a novel therapeutic strategy for diabetic cardiomyopathy. Abstract: Diabetic cardiomyopathy, clinically diagnosed as ventricular dysfunction in the absence of coronary atherosclerosis or hypertension in diabetic patients, is a cardiac muscle-specific disease that increases the risk of heart failure and mortality. Its clinical course is characterized initially by diastolic dysfunction, later by systolic dysfunction, and eventually by clinical heart failure from an uncertain mechanism. Light microscopic features such as interstitial fibrosis, inflammation, and cardiomyocyte hypertrophy are observed in diabetic cardiomyopathy, but are common to failing hearts generally and are not specific to diabetic cardiomyopathy. Electron microscopic studies of biopsy samples from diabetic patients with heart failure have revealed that the essential mechanism underlying diabetic cardiomyopathy involves thickening of the capillary basement membrane, accumulation of lipid droplets, and glycogen as well as increased numbers of autophagic vacuoles within cardiomyocytes. Autophagy is a conserved mechanism that contributes to maintaining intracellular homeostasis by degrading long-lived proteins and damaged organelles and is observed more often in cardiomyocytes within failing hearts. Diabetes mellitus (DM) impairs cardiac metabolism and leads to dysregulation of energy substrates that contribute to cardiac autophagy. However, a "snapshot" showing greater numbers of autophagic vacuoles within cardiomyocytes may indicate that autophagy is activated into phagophore formation or is suppressed due to impairment of the lysosomal degradation step. Recent in vivo studies have shed light on the underlying molecular mechanism governing autophagy and its essential meaning in the diabetic heart. Autophagic responses to diabetic cardiomyopathy differ between diabetic types: they are enhanced in type 1 DM, but are suppressed in type 2 DM. This difference provides important insight into the pathophysiology of diabetic cardiomyopathy. Here, we review recent advances in our understanding of the pathophysiology of diabetic cardiomyopathy, paying particular attention to autophagy in the heart, and discuss the therapeutic potential of interventions modulating autophagy in diabetic cardiomyopathy.